Bioaugmentation Technology for Treatment of Toxic and Refractory Organic Waste Water Based on Artificial Intelligence - Yanbo, Jiang; Jianyi, Jiang; Xiandong, Wei; Wei, Ling; Lincheng, Jiang (Frontiers in Bioengineering and Biotechnology, 2021)
With the development of modern chemical synthesis technology, toxic and harmful compounds increase sharply. In order to improve the removal efficiency of refractory organic matter in waste water, the method of adding powdered activated carbon (PAC) to the system for adsorption was adopted. Through the analysis of organic matter removal rule before and after waste water treatment, it can be found that PAC is easy to adsorb hydrophobic organic matter, while activated sludge is easy to remove hydrophilic and weakly hydrophobic neutral organic matter. PAC-AS system is obviously superior to AS and PAC system in removing organic matter of hydrophilic and hydrophobic components, that is, biodegradation and PAC adsorption are additive. Compared with the control system, the COD removal rate of refractory substances increased by 8.36%, and PAC had a good adsorption effect on small molecular weight organic compounds, but with the increase of molecular weight of organic compounds, the adsorption effect of PAC gradually weakened, and it had no adsorption effect on macromolecular organic compounds. Based on the research of fuzzy control theory, an Agent control system for ozone oxidation process of industrial waste water based on MAS (Mobile Agent Server) theory was established, which was realized by fuzzy control method. The simulation results showed strong stability and verified the feasibility and adaptability of the distributed intelligent waste water treatment system based on MAS theory in the actual control process.